Design of titanium alloy uncemented femoral stems for hip prosthesis suitable for the young adult population (2023)
The hip is one of the human anatomical parts that support the weight of the body and performs rotating movements. In addition, the one that presents the most complications. The incidence of cases in the world of failure of this anatomical part is due to the wear of the acetabulum and fractures of the femur produced by osteoarthritis and rheumatoid arthritis, which causes pain, stiffness, swelling and limited movement of the hip. A successful solution to this problem is the hip prosthesis, manufactured over the last century, improving, and even fully alleviating the effects on the patients. In any case, the hip prosthesis is a mechanical element foreign to the body that can fail, caused by aseptic loosening, deep periprosthetic infection, periprosthetic femoral fractures, dislocations, technical errors, and fracture of the implant. One strategy to reduce hip failures is to improve the lifespan of femoral stems for the increasing number of younger patients undergoing total hip arthroplasty due to the increase lifetime expectation of the patient with a more active lifestyle, requiring prostheses with enhanced designs capable of withstanding the mechanical requirements. This research project aims to design a femoral stem for the Colombian young adult population measuring performance by means of non-clinical mechanical testing. Initially, a selection methodology of femoral stems according to the cross section and the maximum stresses was designed to evaluate the maximum stresses in the femoral stem, decreasing the stiffness of the stem, thus reducing the stress shielding effect in the patient bones. A theoretical, computational, and experimental evaluation of the stresses was performed with a maximum average difference of less than 7.5%. Also, the formulation of a new selection methodology, optimizing the area needed for withstand the loads and decreasing the overall stiffness of the stem.